The Contribution of Internal Audit to the Performance of the Internal Control System - Daif, Achraf; Jalal, Azegagh (European Scientific Journal, ESJ, 2022)
Internal control is increasingly seen as the foundation on which the company relies to ensure, on the one hand, the effectiveness and efficiency of operations, the quality of information and compliance with laws, regulations and policies, and on the other hand, to prevent and control risks that may affect the achievement of objectives. Therefore, internal control encompasses all the different types of security that exist within the organisation to provide reasonable assurance that objectives are achieved. In short, through the deployment of an effective and efficient internal control system, a company is better equipped to achieve its objectives and avoid pitfalls and imponderables. Furthermore, internal auditors are part of the steering framework. Thus, they have the possibility to carry out evaluations, whether permanent or punctual, on the other elements of internal control. Therefore, internal audit is an element of the internal control system, and its purpose is to ensure that all the company’s operations are under control and that the company is managed efficiently and transparently. The ultimate objective of our research is to analyse the role of internal audit as a performance tool of the internal control system.